BLINDNESS RELATED TO PRESUMED RETINAL TOXICITY AFTER USING PERFLUOROCARBON LIQUID DURING VITREORETINAL SURGERY. Issue 9 (September 2018) - Méndez-Martínez, Silvia; Calvo, Pilar; Rodriguez-Marco, Nelson Arturo; Faus, Fernando; Abecia, Emilio; Pablo, Luis
Abstract : Purpose: To describe the presumed retinal toxicity after using specific batches of perfluorocarbon liquid ALA OCTA (Alamedics, Dornstadt, Germany) in pars plana vitrectomy. Methods: This is an observational retrospective consecutive case series analyses of patients operated on pars plana vitrectomy for retinal detachment or intraocular lens subluxation, using the 150141 or 200114 batches of perfluorocarbon liquid ALA OCTA as assistance during the surgery in a single center. Patients were included in this report if they manifested retinal toxicity signs throughout the follow-up, such as retinal and retinal pigment epithelium atrophy, disk paleness, and intensive macular fibrosis. Spectral domain optical coherence tomography (Spectralis; Heidelberg Engineering, Heidelberg, Germany) and Ultra-Wide Field 200° retinal camera (Optos P200Tx; Optos, Scotland, United Kingdom) images, electrophysiological tests, and visual fields were performed to analyze the retinal structure and functionality. Results: Seven of 80 patients showed all the described signs of toxicity, after a mean follow-up of 34.29 days (range: 10–87) since surgery. Four patients needed a second pars plana vitrectomy because of tractional retinal detachment and proliferative vitreoretinopathy, and two of them underwent a third surgery because of redetachment. All patients experienced amaurosis or central scotoma, with a final best-corrected visual acuity ranging from 20/200 to light perception. Conclusion: Presumed toxic batches of perfluorocarbon liquid may cause massive retinal toxicity. A rapid suspicion, a correct traceability of surgical products, and informing health authorities are fundamental to prevent further cases of toxicity. Abstract : Seven cases of massive retinal necrosis after pars plana vitrectomy assisted by two specific batches of ALA OCTA perfluorocarbon (Alamedics, Germany) are exposed in this article. Retinal patchy atrophy, disk paleness, macular fibrosis, and poor visual acuities were possible toxic signs found in these patients.